2019
DOI: 10.3389/fonc.2019.00487
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Multidrug Resistance in Cancer by Multi-Functional Flavonoids

Abstract: Multidrug resistance (MDR) resulting from different defensive mechanisms in cancer is one of the major obstacles of clinical treatment. To circumvent MDR many reversal agents have been developed, but most of them fail in clinical trials due to severely adverse effects. Recently, certain natural products have been reported to overcome MDR, including flavonoids which are abundant in plants, foods, and herbs. The structure of flavonoids can be abbreviated as C6-C3-C6 (C for carbon), and further categorized into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 238 publications
(253 reference statements)
0
81
1
Order By: Relevance
“…[ 25 ] Researchers reported that flavonoids and iso‐flavonoids possess multiple bioactivities and can either kill or resensitise conventional chemotherapeutics to resistant cancer cells. [ 26 ] So we are in search of a novel angiosarcoma‐targeting agent that has minimal side effects and null tumour resistance nature and can be suitable for old patients with angiosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Researchers reported that flavonoids and iso‐flavonoids possess multiple bioactivities and can either kill or resensitise conventional chemotherapeutics to resistant cancer cells. [ 26 ] So we are in search of a novel angiosarcoma‐targeting agent that has minimal side effects and null tumour resistance nature and can be suitable for old patients with angiosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Due to toxicity and lack of specificity of synthetic MDR agents, recent researches have focused on beneficial effects of natural compounds in overcoming MDR in cancer. According to recent research, polyphenols might overcome MDR through various mechanisms, which will be further discussed in our work [32][33][34][35].…”
Section: Introductionmentioning
confidence: 92%
“…For each azaaurone, carbon, hydrogen, and nitrogen atoms were analyzed and were found in nearly full (96-98%) agreement with the expected values. The compounds were fully characterized by 1 H NMR, 13 C NMR, and high-resolution mass spectrometry (HRMS) (data shown in Supplementary Materials, Table S5).…”
Section: Synthesis Of Azaaurones 1-13mentioning
confidence: 99%
“…We screened a library of 140 compounds consisting of flavonoidic derivatives and thiosemicarbazones (Figure 1, full structures are provided in Supplementary Materials, Table S1). Flavonoidic derivatives have been widely studied as candidates for cancer treatment and prevention, with various naturally occurring substances reported to be effective against resistant tumors [13,14]. On the other hand, thiosemicarbazones were included since several compounds belonging to this class have been reported to possess increased toxicity against otherwise drug-resistant cells [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%